Health seeking behaviour in pulmonary tuberculosis: a cross sectional study - J., Jebamalar; Senthilkumar, Priya; Ramola, Mary (International Journal Of Community Medicine And Public Health, 2018)
Background: Health seeking behaviour has been identified as a complex and dynamic process which influences disease burden of tuberculosis. The present study aimed to study health seeking behaviour among pulmonary tuberculosis patients in a metropolitan city and to assess diagnostic and treatment delays and their determinants. Methods: A cross sectional study was conducted among newly diagnosed pulmonary tuberculosis patients registered for intensive phase of Category 1 ATT during the study period in Zone VIII of Chennai Corporation. The sample size was 197. The study was conducted over a period of one year from September 2015 to August 2016. A standardized WHO interview schedule on diagnostic delay was used for the study. Results: Patients sought healthcare for more severe symptoms like hemoptysis (delay of 38 days) earlier than for cough (delay o- 8 days). Other reasons for delay in seeking care were hope of self-resolution, financial constraints, fear of what the diagnosis would be, incompatible timings etcetera. The total mean delay from onset of symptoms till start of treatment was around 47 days, out of which the patient delay was 42 days. Factors significantly associated with delay included smoking, age more than 35 years and not approaching healthcare facilities first. Conclusions: An unacceptably high patient delay is the major contributor to total delay in the diagnosis and treatment of pulmonary tuberculosis patients. There is increased odds of delay among smokers compared to those who have never smoked. So smokers may be added to the high risk group for suspicion of tuberculosis for fast tracking of diagnosis and treatment. Furthermore, methods to curb over the counter medications should be explored.